2013
DOI: 10.1371/journal.pone.0077629
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomics of Slow vs. Rapid Motor Progression Parkinson’s Disease: a Pilot Study

Abstract: Progression of Parkinson’s disease (PD) is highly variable, indicating that differences between slow and rapid progression forms could provide valuable information for improved early detection and management. Unfortunately, this represents a complex problem due to the heterogeneous nature of humans in regards to demographic characteristics, genetics, diet, environmental exposures and health behaviors. In this pilot study, we employed high resolution mass spectrometry-based metabolic profiling to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 36 publications
(47 reference statements)
5
90
0
1
Order By: Relevance
“…N8-acetyl spermidine increased in individuals with rapidly progressing PD compared to individuals with slow progressing PD. Altered polyamine metabolism in PD Roede et al (2013) Human Plasma LC-ECA 8-Hydroxy-2-deoxyguanosine levels and glutathione significantly increased in PD patients. Uric acid was significantly reduced Bogdanov et al (2008) Human Postmortem CSF LC and GC-mass spec.…”
Section: Huntington's Diseasementioning
confidence: 98%
“…N8-acetyl spermidine increased in individuals with rapidly progressing PD compared to individuals with slow progressing PD. Altered polyamine metabolism in PD Roede et al (2013) Human Plasma LC-ECA 8-Hydroxy-2-deoxyguanosine levels and glutathione significantly increased in PD patients. Uric acid was significantly reduced Bogdanov et al (2008) Human Postmortem CSF LC and GC-mass spec.…”
Section: Huntington's Diseasementioning
confidence: 98%
“…PD patients suffer from a very heterogeneous progression of motor degeneration and that variability hampers PD biomarker discovery. In order to find out the biochemical processes responsible for progression velocity and potentially useful biomarkers for PD prognosis, Roede et al (2013) evaluated 100 serum samples (Roede et al, 2013). Serum was obtained from 39 and 41 PD patients with rapid and slow progression, respectively, as well as 20 control subjects.…”
Section: Blood-based Metabolomics In Pdmentioning
confidence: 99%
“…Most of the metabolites could not be identified via database matches. Data from high-resolution MS from those unknowns showed matches with numerous phytochemicals, suggesting dietary ingredients might protect against disease development (Roede et al, 2013).…”
Section: Blood-based Metabolomics In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…In a pilot study, N8-acetyl spermidine was found to be significantly elevated in the rapid progressors compared to both control subjects and slow progressors. The exploratory data indicate that a fast motor progression disease phenotype can be distinguished early in disease using high resolution mass spectrometry-based metabolic profiling, and that altered polyamine metabolism may be a predictive marker of rapidly progressing PD [59].…”
Section: Metabolomicsmentioning
confidence: 99%